2011
DOI: 10.1007/s11116-011-9323-3
|View full text |Cite
|
Sign up to set email alerts
|

Can rural older drivers meet their needs without a car? Stated adaptation responses from a GPS travel diary survey

Abstract: Rural seniors are highly dependent on their automobile to meet their trip making needs, yet the effects of aging can make access to the vehicle difficult or impossible over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In rural areas, car access is often a precondition for independent life (cf. Ahern & Hine, 2012;Hanson & Hildebrand, 2011). In line with this, Mollenkopf (2002) showed that satisfaction with mobility options in rural areas is-among other factors-determined by car access, while this is not the case in urban areas.…”
Section: Built Environmentmentioning
confidence: 63%
See 1 more Smart Citation
“…In rural areas, car access is often a precondition for independent life (cf. Ahern & Hine, 2012;Hanson & Hildebrand, 2011). In line with this, Mollenkopf (2002) showed that satisfaction with mobility options in rural areas is-among other factors-determined by car access, while this is not the case in urban areas.…”
Section: Built Environmentmentioning
confidence: 63%
“…Older women walk more often and travel more by public transport, whereas older men drive more frequently. When travelling in a personal vehicle, older women are more often passengers and not drivers (Hanson & Hildebrand, 2011;Li et al, 2012;Rosenbloom, 2006;Siren & Hakamies-Blomqvist, 2006) and not all gender differences in mode choice can be explained by differences in licensing and car availability Le Vine & Jones, 2012).…”
Section: Gendermentioning
confidence: 99%
“…This study Therefore, it may be postulated that the ageing population in developed countries is becoming increasingly car dependent and less likely to use alternative transport [38]. This reliance seems to be particularly evident in suburban [34,40] and rural environments [32,35,41]. Tacken [42] highlighted that "mobility behavior follows the general rule that people stay as long as possible with the type of behavior they are used to".…”
Section: Methodsmentioning
confidence: 95%
“…Stopping driving can be perceived as a loss of independence [19,29] and is strongly associated with symptoms of depression [30,31]. Furthermore, the car remains the preferred mode of transport once driving has been given up, since asking for a lift from family or friends is considered the first option for people who cannot drive [18,19,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…When travelling in a car, older men are more often drivers and women are more often passengers [20][21][22][23][24]. A common phenomenon is that women drive less as they age, finally ceasing driving because their husbands are the main drivers.…”
Section: Introductionmentioning
confidence: 99%